General Synthetic Strategy to Ordered Mesoporous Carbon Catalysts with Single‐Atom Metal Sites for Electrochemical CO2 Reduction. Issue 16 (1st March 2022) - Luo, Zhicheng; Yin, Zhouyang; Yu, Jiaqi; Yan, Yu; Hu, Bing; Nie, Renfeng; Kolln, Anna F.; Wu, Xun; Behera, Ranjan K; Chen, Minda; Zhou, Lin; Liu, Fudong; et al.
Abstract: The electrochemical carbon dioxide reduction reaction (CO2 RR) is a transformative technology to reduce the carbon footprint of modern society. Single‐site catalysts have been demonstrated as promising catalysts for CO2 RR, but general synthetic methods for catalysts with high surface area and tunable single‐site metal composition still need to be developed to unambiguously investigate the structure–activity relationship crossing various metal sites. Here, a generalized coordination–condensation strategy is reported to prepare single‐atom metal sites on ordered mesoporous carbon (OMC) with high surface areas (average 800 m 2 g ‐1 ). This method is applicable to a broad range of metal sites (Fe, Co, Ni, Cu, Pt, Pd, Ru, and Rh) with loadings up to 4 wt.%. In particular, the CO2 RR to carbon monoxide (CO) Faradaic efficiency (FE) with Ni single‐site OMC catalyst reaches 95%. This high FE is maintained even under large current density (>140 mA cm ‐2 ) and in a long‐term study (14 h), which suits the urgently needed large‐scale applications. Theoretical calculations suggest that the enhanced activity on single‐atom Ni sites results from balanced binding energies between key intermediates, COOH and CO, for CO2 RR, as mediated by the coordination sphere. Abstract : A benchmark study of various single‐atom transition metal catalysis is achieved for electrochemical reduction of CO2 to CO. The single‐atom Ni anchored on ordered mesoporous nitrogen assembly carbon catalyst, Ni‐NAC, possesses not only high CO selectivity and current density, but also high durability in a broad potential range.